Effect of age, sex and body weight on the serum concentrations of cobalamin and folate in cats consuming a consistent diet. Issue 2 (February 2018) - Hill, Sarah A; Cave, Nicholas J; Forsyth, Sandra
Objectives: Multiple feline diseases involving the gastrointestinal tract, pancreas, liver and biliary tract are known to cause abnormal serum cobalamin and folate concentrations. Measuring the serum concentration of these vitamins can therefore be a helpful diagnostic tool. However, factors other than disease, in particular age, have also been suggested to have an effect on the serum concentration of cobalamin and folate. In previous studies, the dietary intake was not standardised, or even known, despite diet being the prinicpal source of both vitamins. Therefore, we evaluated the effect of age, sex and body weight on the serum concentration of folate and cobalamin in cats fed the same diet. Methods: The serum cobalamin and folate concentrations were measured in 65 apparently healthy cats in a nutrition colony that had been fed an identical diet. A linear model was used to test the relationship between the serum concentration of cobalamin and folate with the variables age, sex and body weight. Results: There was a large variation in the serum concentration of both folate and cobalamin, despite identical intake. Serum cobalamin was inversely associated with age ( P = 0.002), and males had higher concentrations than females ( P = 0.039). Serum folate was positively associated with age ( P = 0.01). Conclusions and relevance: Independent of diet, serum cobalamin concentration decreases with age. Changes in gastrointestinal function, microflora or metabolism may be responsible. Older cats may be more susceptible to cobalamin deficiency secondary to inappetence or gastrointestinal disease.